2002
DOI: 10.1046/j.1440-1592.2002.00265.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of protein kinase A in the inhibition of human mast cell histamine release by β-adrenergic receptor agonists

Abstract: Background:  Although β‐adrenergic receptor agonists inhibit antigen‐induced release of histamine, leukotrienes and prostaglandin D2 from human lung fragments, dispersed human lung mast cells and human skin mast cells, subcellular mechanisms for the inhibition of histamine release by β‐adrenergic receptor agonists are not well delineated. The aim of the present study was to investigate the inhibitory mechanisms of β‐adrenergic receptor agonists for human mast cell histamine release using human cultured mast ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…[10][11][12][13] We also reported that b 2 -adrenoceptor agonists inhibit the chemical mediator release in cultured human mast cells. [14][15][16] b 2 -Adrenoceptor agonists inhibit mediator release from human mast cells far more potently than disodium cromoglycate. 6,8,13,14) Furthermore, b 2 -adrenoceptor agonists inhibit PGD 2 and LT release more potently than histamine release from human mast cells.…”
mentioning
confidence: 99%
“…[10][11][12][13] We also reported that b 2 -adrenoceptor agonists inhibit the chemical mediator release in cultured human mast cells. [14][15][16] b 2 -Adrenoceptor agonists inhibit mediator release from human mast cells far more potently than disodium cromoglycate. 6,8,13,14) Furthermore, b 2 -adrenoceptor agonists inhibit PGD 2 and LT release more potently than histamine release from human mast cells.…”
mentioning
confidence: 99%
“…Studies have shown that β-adrenergic receptor agonists inhibit IgE-dependent histamine release by human mast cells ( 26 ) and that exposing healthy volunteers to salmeterol and terbutaline attenuates the cutaneous mast cell response for up to 24 h postexposure ( 27 ). However, it is not known whether these inhibitory effects follow a dose–response curve nor whether they are durable with molecules such as adrenaline, the first-line treatment for anaphylaxis and used in large quantities, as in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…20,21,22,23,24 The description of the change from positive to negative skin test in a patient allergic to carboplatin after desensitization provides evidence that mast cell inhibitory mechanisms do not need massive release of mediators. 25 Studies have shown that β-adrenergic receptor agonists inhibit IgE-dependent histamine release by human mast cells, 26 and that exposing healthy volunteers to salmeterol and terbutaline attenuates the cutaneous mast cell response for up to 24 hours post-exposure. 27 However, it is not known whether these inhibitory effects follow a dose-response curve, nor whether they are durable with molecules such as adrenaline, the first-line treatment for anaphylaxis and used in large quantities in our patient's case.…”
Section: Discussionmentioning
confidence: 99%